2010
DOI: 10.2319/101509-577.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of resin-modified orthodontic band adhesives

Abstract: ) were prepared and the samples were extracted in 3 mL of Basal Medium Eagle with 10% newborn calf serum for 24 hours. The L929 cells were plated (25,000 cells/mL) in wells of 96-well dishes and maintained in a humidified incubator for 24 hours at 37uC, 5% CO 2 , and 95% air. After 24-hour incubation of the cells, the incubation medium was replaced by the immersed medium in which the samples were stored. Then L929 cells were incubated in contact with eluates for 24 hours. The cell mitochondrial activity was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…After the period of 7 days, the RMO ® and Transbond ® demonstrated intense inflammatory infiltrate when compared with the control group (P=0.004). This initial inflammatory response reflected the attempt by the tissue to induce the process of degradation of the materials through the inflammatory cells recruited to the surrounding tissue and in the direction towards the surface of the cements (Ghanaati et al 2010, Malkoc et al 2010. In addition, it suggested that the elution of toxic substances released by these cements was capable of stimulating the production of reactive oxygen species (ROS), and increasing the expression of COX-2/PGE 2, which are potent chemical mediators, capable of potentiating the inflammatory response (Costa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the period of 7 days, the RMO ® and Transbond ® demonstrated intense inflammatory infiltrate when compared with the control group (P=0.004). This initial inflammatory response reflected the attempt by the tissue to induce the process of degradation of the materials through the inflammatory cells recruited to the surrounding tissue and in the direction towards the surface of the cements (Ghanaati et al 2010, Malkoc et al 2010. In addition, it suggested that the elution of toxic substances released by these cements was capable of stimulating the production of reactive oxygen species (ROS), and increasing the expression of COX-2/PGE 2, which are potent chemical mediators, capable of potentiating the inflammatory response (Costa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This material has been increasingly used by orthodontists for cementing orthodontic bands, due to the favorable physical and chemical properties capable of providing good retentiveness, fluoride release capacity and being practical to use (Malkoc et al 2010). However, there are indications that this cement may present cytotoxicity, genotoxicity and inadequate biocompatibility (Angelieri et al 2011, Selimović-Dragaš et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study demonstrated that many resinbased dental cement materials create toxic reactions in different cell cultures [1][2][3]7,16) . The effects of five different luting resin cements on bDPCs were investigated, using the same standardized real-time xCELLigence test system for each.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of resin-based restorative materials has been extensively studied, but only a few studies on the cytotoxicity of resin luting cements have been presented. The toxicities of the resin luting cements have been evaluated, and different test methods and cells, including the murine fibroblast cell line L929 5) , primary cultures of human lymphocytes 6) , human gingival fibroblasts 7) , and human dental pulp cell cultures 3) have been utilized. In previous experiments, several methods were used to evaluate the cytotoxicity of resin materials: lactate dehydrogenase (LDH) assay 8) , benzol-disulfonate (WST-1) assay 9) , benzene sulfonic acid hydrate assay, tetrazolium bromide (MTT) assay 10) , bromodeoxiuridine (BrdU) assay 8) , and fluorescence microscopy 11,12) .…”
Section: Introductionmentioning
confidence: 99%